The use of behavioural theories in end-of-life care research: A systematic review. (June 2018) - Scherrens, Anne-Lore; Beernaert, Kim; Robijn, Lenzo; Deliens, Luc; Pauwels, Nele S; Cohen, Joachim; Deforche, Benedicte
Background: It is necessary to understand behaviours that contribute to improvement in the quality of end-of-life care; use of behavioural theories allows identification of factors underlying end-of-life care behaviour, but little is known about the extent to which, and in what manner, these theories are used in an end-of-life care research context. Aim: To assess the number of end-of-life care studies that have used behavioural theories, which theories were used, to what extent main constructs were explored/measured and which behavioural outcomes were examined. Design: We conducted a systematic review. The protocol was registered on PROSPERO (CRD42016036009). Data sources: The MEDLINE (PubMed), PsycINFO, EMBASE, Web of Science and CINAHL databases were searched from inception to June 2017. We included studies aimed at understanding or changing end-of-life care behaviours and that explicitly referred to individual behavioural theories. Results: We screened 2231 records by title and abstract, retrieved 43 full-text articles and included 31 studies – 27 quantitative (of which four (quasi-)randomised controlled trials) and four qualitative – for data extraction. More than half used the Theory of Planned Behaviour (9), the Theory of Reasoned Action (4) or the Transtheoretical Model (8). In 9 of 31 studies, the theory was fully used, and 16 of the 31 studies focussed on behaviours in advance care planning. Conclusion: In end-of-life care research, the use of behavioural theories is limited. As many behaviours can determine the quality of care, their more extensive use may be warranted if we want to better understand and influence behaviours and improve end-of-life care.